Hemoglobin Levels and Number of Erythrocytes in Scabies-infected Male Mice (Mus musculus) Treated with Water Extract of Taro (Colocasia esculenta (L.) Schott Cultivar Hideung - Nia Yuliani; Ananda Sarah Nur Azizah; Widhyastini, I Gusti Ayu Manik (Sains Natural: Journal of Biology and Chemistry, 2024)
This study aims to analyze the hemoglobin levels and number of erythrocytes in scabies-infected male mice treated with taro water extract as a cheap and safe alternative treatment for scabies. The test animals were 24 mice weighing 20-25 grams, divided into 6 groups consisting of: K1: taro water extract 100gr/100 ml water, K2 taro water extract 200gr/100ml water, K3: using 300gr/100ml taro water extract water, K4: ivermectin positive control, K5: negative control with water alone, and K6 normal control not infected with scabies and not given treatment. The application of taro extract was carried out for five days. Observations were carried out every day, until day 7. Blood samples were taken from mice three times: before being infected with scabies (healthy), when infected with scabies, and after being treated with taro water extract. The data obtained was processed statistically using the SPSS software with the One Way ANOVA test. Sarcoptes scabiei infection affects the appearance of the blood profile of male mice when infected, there is an increase in the number of erythrocytes but does not affect hemoglobin levels. Treatment with water extract of the taro (Colocasia esculenta (L.) Schott) cultivar hideung in different concentrations did not show significant blood results, but it could heal wounds caused by scabies infection.